What the future holds: cystic fibrosis and aging - Blankenship, Sydney; Landis, Aaron R.; Harrison Williams, Emily; Peabody Lever, Jacelyn E.; Garcia, Bryan; Solomon, George; Krick, Stefanie (Frontiers in Medicine, 2024)
Cystic fibrosis (CF) is one of the most common genetic diseases with around 70,000 affected patients worldwide. CF is a multisystem disease caused by a mutation in the CF transmembrane conductance regulator gene, which has led to a significant decrease in life expectancy and a marked impairment in the quality of life for people with CF (pwCF). In recent years, the use of highly effective CFTR modulator therapy (HEMT) has led to improved pulmonary function, fewer CF exacerbations, lower symptom burden, and increased weight. This has coincided with an increased life expectancy for pwCF, with mean age of survival being now in the 50s. This being a major breakthrough, which the CF population has hoped for, pwCF are now facing new challenges by growing old with a chronic respiratory disease. In this mini review, we are attempting to summarize the current knowledge of the aging process and its effect on CF disease and its manifestations including new developments, the current research gaps and potential future developments in the field to allow healthy aging for the CF community.